ANALISIS TINDAK TUTUR DIREKTIF DALAM DIALOG FILM “RUMAH UNTUK ALIE” KARYA LENN LIU - Nur Maharani S; Yusmah Yusmah; Suardi Zain; Muhammad Hanafi (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
The purpose of this study is to identify and classify the forms and functions of directive speech acts in the characters' dialogues. This study uses a qualitative approach with a descriptive type because it focuses on the analysis of non-numerical data from the film, in the form of speech and visuals. The main focus of the study includes the forms and functions of directive speech acts that appear in the characters' dialogues. The research data were obtained from the dialogues or speeches of the characters in the film, while the source of the research data was the film Rumah untuk Alie by Lenn Liu, produced by Falcon Pictures and released on the digital platform Netflix in 2025. The data collection techniques used included listening and note-taking techniques. The results of the study show that directive speech acts in the film “Rumah untuk Alie” consist of several forms and functions. In the directive declarative form, five functions were found, namely the request function of 16 data, the command function of 3 data, the prohibition function of 10 data, the permission function of 5 data, and the suggestion function of 9 data. The interrogative form has four functions, namely the request function of 6 data, the question function of 89 data, the command function of 1 data, and the prohibition function of 1 data. Meanwhile, the imperative form found five functions, namely the request function of 29 data, the command function of 21 data, the prohibition function of 7 data, the permission function of 1 data, and the suggestion function of 5 data.